THE PRODUCTIVITY OF TURMERIC (CURCUMA LONGA) AS INFLUENCED BY NUTRIENTS AND RHIZOMES SIZE GROWN IN MAKURDI, BENUE STATE, NIGERIA - Ankaau, I. B.; Odiaka, N. I.; Madina, P.` (FUDMA Journal of Sciences, 2020)
The experiment was carried out at Agronomy Teaching and Fesearch Farm of Federal University of Agriculture at 7â—‹ 38Nand longitude 8â—‹ 38E and 97m above sea level in southern guinea savannah agro-ecological zone of Nigeria to investigate the productivity of Turmeric (Curcuma longa) as influenced by nutrients and rhizomes size grown in Makurdi, Benue State. The experiment was laid in a Randomized Complete Block Design (RCBD) with three replications. Treatment were cow dung 5t/ha, poultry droppings 5t/ha, NPK fertilizer at 0.22t/ha and control and the rhizomes sets used are small set (S1) and large set (S2). Data collected were number of leaves, plant height, Number of plant per hill fourth nightly after emergence (WAE) and yield weight was taken during harvest. The data were analysed using (ANOVA) which indicated that Poultry droppings shows superiority over the other treatment used and large set of rhizomes supersede the small set rhizomes used